Pengungkapan Diri (Self Disclosure) melalui Fitur Instagram Story pada Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah - Indah Pratiwi Pratiwi; Siti Nurkholisa Pradini Mukhtaruddin (Journal of Communication Sciences (JCoS), 2023)
This study aims to find out how self-disclosure on the Instagram Stories feature is carried out by Communication Science Students at the University of Muhammadiyah Makassar. The research method used is descriptive qualitative research by interviewing three Communication Science students as respondents who have Instagram accounts and using Instagram Stories frequently. As for the results of the study, namely the number or frequency of the number and time of self-disclosure messages is influenced by the size of the topic discussed, the comparison or quality of self-disclosure is supported by the presence and effort motivation, accuracy is based on how individuals frame information about themselves, goals are influenced by self-control and dyadic effects, and intimacy based on the influence of a sense of togetherness, such as the Johari Window classification (open self).